Plant Growth Promoting Rhizobacteria in Plant Health: A Perspective Study of the Underground Interaction - Mudasir Ahmad Bhat; Awdhesh Kumar Mishra; Saima Jan; Mujtaba Aamir Bhat; Mohammad Azhar Kamal; Safikur Rahman; Ali Asghar Shah; Arif Tasleem Jan (Plants, 2023)
Plants are affected by various environmental stresses such as high or low temperatures, drought, and high salt levels, which can disrupt their normal cellular functioning and impact their growth and productivity. These stressors offer a major constraint to the morphological, physiological, and biochemical parameters; thereby attributing serious complications in the growth of crops such as rice, wheat, and corn. Considering the strategic and intricate association of soil microbiota, known as plant growth-promoting rhizobacteria (PGPR), with the plant roots, PGPR helps plants to adapt and survive under changing environmental conditions and become more resilient to stress. They aid in nutrient acquisition and regulation of water content in the soil and also play a role in regulating osmotic balance and ion homeostasis. Boosting key physiological processes, they contribute significantly to the alleviation of stress and promoting the growth and development of plants. This review examines the use of PGPR in increasing plant tolerance to different stresses, focusing on their impact on water uptake, nutrient acquisition, ion homeostasis, and osmotic balance, as well as their effects on crop yield and food security.